Impact of Israeli Colonies on the Grazing Communities in Tubas Governorate,Case Study (Almaleh and Beduin Areas) - Fatin Ahmed Awad Qassrawi (My University, 2016)
Tubas and Northern Jordan Valley Governorate face the risk of Israeli colonial deployment on its territory. Since 1967, Israeli occupation has continued the establishment of settlements so as to control the area. It has in the beginning established Mekhola Colony, the first Agricultural Colony, followed by six other colonies built on scattered area of land as area C in the Governorate according to Oslo interim agreement of military camps, roads, segregation and other colonial actions. The present study describes the geographical spread of Israeli colonies in Tubas and the Jordan Valley Governorate, and other colonial procedures or Israeli violations. And it also describes the Israeli practices against countryside communities in the Governorate , as well as it clarifies the extent of the impact of these colonies on the village of Al-Maleh and Bedouin population in various aspects. The study used the historical approach to investigate the impact of the emergence of Israeli colonization in the West Bank. The study also used the descriptive analytical deductive method to get to know the impact of Israeli measures resident of the village of Al-Maleh and Bedouin communities. The study concluded that the colonies in Tubas was clarified the increasing of colonists, which was accompanied with their expansion on the expense of the people. The accounted land to colonies, outposts and Israeli military camps are accounted for about 5.5% of Tubas and Northern Jordan Valley area. The study also found that the Israeli occupation has carried a numerous violations against the population of the country side communities in Tubas; which aims to force people leave their. The study also found that Israeli measures affected negatively the demographic, educational, health, physical, economic and service fields contention of the people the impact of the Israeli settlements in Tubas on the village of al-Maleh and Bedouin communities. The study recommended that the Palestinian Authority should pay more attention to the grazing areas and provide them with public services and facilities. The study also recommended on activating the role of the Palestinian media by highlighting the suffering of such communities and the Israeli violations to the Arab and foreign word.

تواجه محافظة طوباس والأغوار الشمالية خطر الانتشار الاستيطاني على أراضيها. فمنذ عام 1967م عمل الاحتلال الإسرائيلي على إنشاء المستعمرات على أراضي المحافظة؛ لتثبيت سيطرته عليها, ولذلك أنشأ فيها أول مستعمرة زراعية وهي مستعمرة ميخولا, ثم تلتها ستة مستعمرات أقيمت على مساحات متناثرة من الأراضي المصنفة كمناطق C في المحافظة وفقا لاتفاقية أوسلو المؤقتة ومن ثم معسكرات الجيش، والطرق، وجدار الفصل العنصري وغير ذلك من الإجراءات الاستعمارية. وتأتي هذه الدراسة لتوضح الانتشار الجغرافي للمستعمرات الإسرائيلية في محافظة طوباس والأغوار الشمالية والإجراءات الاستعمارية الأخرى. كما توضح الانتهاكات الإسرائيلية الممارسة ضد سكان التجمعات الرعوية في المحافظة, بالإضافة إلى توضيح مدى تأثير هذه المستعمرات على قرية المالح والمضارب البدوية في جوانب متعددة. وقد استخدم في الدراسة المنهج التاريخي بقصد القاء الضوء على نشأة الاستعمار الاستيطاني الإسرائيلي في الضفة الغربية ومراحله. بالإضافة إلى استخدام المنهج الوصفي التحليلي والإستنتاجي لمعرفة تأثير المستعمرات على سكان قرية المالح والمضارب البدوية. ولقد توصلت الدراسة إلى أن هنالك تطور في أعداد المستعمرين, والتي رافقها توسع في المستعمرات على حساب أراضي الأهالي, بحيث شكلت نسبة الأراضي المخصصة للمستعمرات والبؤر الاستيطانية والمعسكرات الإسرائيلية حوالي 5.5% من مساحة محافظة طوباس والأغوار الشمالية. أيضا توصلت الدراسة إلى قيام الاحتلال الإسرائيلي بانتهاكات عديدة ضد سكان التجمعات الرعوية في محافظة طوباس؛ والتي تهدف إلى ترحيل الأهالي. كما توصلت الدراسة إلى تأثير المستعمرات الإسرائيلية في محافظة طوباس سلبا على قرية المالح والمضارب البدوية في المجالات الديموغرافية والتعليمية والصحية والعمرانية والاقتصادية والخدماتية. وأوصت الدراسة بأن على السلطة الفلسطينية أن تولي اهتماما أكبر للمناطق الرعوية وتوفر لهم الخدمات والمرافق العامة. وأوصت أيضا بضرورة تفعيل دور وسائل الإعلام الفلسطينية من خلال تسليط الضوء على معاناة هذه المجتمعات في المنطقة.
تأثير المستعمرات الإسرائيلية على التجمعات الرعوية في محافظة طوباس - حالة دراسية منطقة المالح والمضارب البدوية